Using video and online subtitling to communicate across languages from West Papua - Crosby, Alexandra (The Australian journal of anthropology, 2014)
In this paper we examine mediated practices and experiences of online translation and subtitling. Our paper is based on a collaboration with EngageMedia − a not-for-profit organisation based in Australia and Indonesia − and is specifically focused on its work in West Papua. We argue that the video-hosting and online subtitling that is enabled through EngageMedia's websites, while mobilising West Papuan stories in a logical, relatively fast and organised manner, is embedded in a more messy socially-mediated translation process that occurs across shifting scales (local, national, regional, and global), and a range of cultures (online, offline, local, global, networked). By examining this socially-mediated process we identify the many ways in which ‘friction’ emerges and we conclude that for video to support multi-lingual, translational communication and activism, social and technological infrastructures need to be further developed to avoid ‘restrictive frictions’ and create ‘productive’ ones.